Bleeding juxtaampular islet cell carcinoma, without jaundice, in a cholecystectomy - Praderi, Raúl; Kamaid, Emil; Verccelli, Jorge; Sojo, Enrique; Praderi, José; Terra, Eneas (Cirugía del Uruguay, 1993)
A 36 year old fema/e who had been cholecystectomyzed because of vesicular lithiasis consulted because of digestive hemorrhage due to an u/cered tumor of papilla which did not obstruct biliar viae. Ampullectomy was performed with microsurgery, calibrating the choledocho-duodenal anastomosis with TTH throug the duodenum. Histology showed it was a malignant insular tumor and immunehistochemistry showed ce/Is the were reactive to somatostatine and pancreatic plypeptide. Evolution was excellent and free of recidive. This case is exceptional in international literature and unique in the national one.